G.I. Joe : a real American hero! Silent missions Vol. 1 - Hama, Larry; Hester, Phil, 1966-; Dani, 1992-; Watters, Dan; Romero, Leonardo; Krahnke, Andrew; Craig, Wes (G.I. Joe : a real American hero!, 2025)
Jump into a collection of five BRAND NEW silent issues from the hottest creators in comics featuring fan favorite G.I. Joe characters! SUPERSTAR CREATORS PRESENT UNFORGETTABLE ALL NEW G.I. JOE SILENT MISSIONS. The face of comic books changed forever when G.I. JOE: A REAL AMERICAN HERO #21 introduced fans to the "Silent Interlude", an action-packed story with NO DIALOGUE. Now, experience the original groundbreaking silent issue plus five ALL NEW silent issues featuring the most popular G.I. Joe characters including Duke, Roadblock, Jinx, Spirit, Beach Head and more from the most acclaimed voices in comics!